Finite Mathematics and Calculus with Applications - Lial, Greenwell, Ritchey; Margaret L. Lial; Raymond Greenwell; Nathan Ritchey (USA Pearson, 2016)
Widely known for incorporating interesting, relevant, realistic applications, this new edition offers more real applications citing real data sources. It also integrates recent recommendations from mathematics educational organizations, and allows for increased visualization and discovery through optional use of graphing calculators.
Keywords: Textbooks; Mathematics; (MFYC07) Mathematics